A novel integrated Urban flood risk assessment approach coupling GeoDetector-Dematel and clustering method - Zheng, Chuanxing; Yang, Weichao; Jiang, Xuelian; Lian, Jijian; Hu, De; Yan, Xue; Yan, Lin (Journal of environmental management, 2024)
Urban flood risk assessment plays a crucial role in disaster prevention and mitigation. A scientifically accurate assessment and risk stratification method are of paramount importance for effective flood risk management. This study aims to propose a comprehensive urban flood risk assessment approach by coupling GeoDetector-Dematel and Clustering Method to enhance the accuracy of urban flood risk evaluation. Based on simulation results from hydraulic models and existing literature, the research established a set of urban flood risk assessment indicators comprising 10 metrics across two dimensions: hazard factors and vulnerability factors, among which vulnerability factors include exposure factors, sensitivity factors, and adaptability factors. Subsequently, the research introduced the GeoDetector-Dematel method to determine indicator weights, significantly enhancing the scientific rigor and precision of weight calculation. Finally, the research employed the K-means clustering method to risk zonation, providing a more scientifically rational depiction of the spatial distribution of urban flood risks. This novel comprehensive urban flood risk assessment method was applied in the Fangzhuang area of Beijing. The results demonstrated that this integrated approach effectively enhances the accuracy of urban flood risk assessment. In conclusion, this research offers a new methodology for urban flood risk assessment and contributes to decision-making in disaster prevention and control measures. [Display omitted] •A novel integrated urban flood risk assessment approach is proposed.•A set of urban flood risk assessment index system is established.•A novel method using GeoDetector-Dematel determines index weights.•K-means method is introduced to obtain more scientific flood risk.